Reducing Poverty through Optimization of Zakat on Agricultural and Profession - Pratama, Siectio Dicko; Yuni, Rezha Nursina (Universitas Muhammadiyah Yogyakarta, 2020)
Zakat is a system in Islam that is designed to allocate the wealth from the rich to the poor and the needy. The effectivity of zakat in reducing poverty has been proven in the history of Islam. Nevertheless, nowadays, Zakat is still unable to eliminate poverty. Bad planning and organizing of zakat are the main reason for that especially the less information about the potency of zakat in each region. Indonesia is a country that is rich in Natural Resources and has many workforces. So, Indonesia may have hidden potential of agricultural and professional zakat. This study tries to calculate the potency and the impact of the zakat on reducing poverty. The effect will be examined descriptively and statistically and also will be presented by mapping all the provinces in Indonesia. The result shows that there are about 16.1 trillion rupiahs of zakat potential furthermore able to reduce the poverty rate in Indonesia for 0.75 percent. DKI Jakarta is the most affected province by zakat because its poverty rate reaches 0.22 percent. To implement this theory in real practice, the utilization of the mosque to distribute zakat funding where BAZNAS represents as the manager is suggested.